2012
DOI: 10.1093/her/cys085
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of North Carolina's state-sponsored youth tobacco prevention media campaign

Abstract: In 2003, the state of North Carolina (NC) implemented a multi-component initiative focused on teenage tobacco use prevention and cessation. One component of this initiative is Tobacco.Reality.Unfiltered. (TRU), a tobacco prevention media campaign, aimed at NC youth aged 11-17 years. This research evaluates the first 5 years of the TRU media campaign, from 2004 to 2009, using telephone surveys of NC youth. Overall, TRU campaign awareness was moderate among youth in its first year, with awareness significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
0
6
1
Order By: Relevance
“…Our longitudinal study of cohorts of 12th graders from a nationally representative sample found no evidence that greater exposure to anti-tobacco media campaigns at baseline was associated with any smoking or daily smoking initiation as youth transitioned into adulthood. Our findings are in contrast to the majority of previously published cross-sectional work, including a study analyzing cross-sectional MTF data from the same time period (2000-2015) [14], which found that higher levels of exposure to antitobacco media campaigns are generally associated with lower likelihoods of smoking intentions [3,6,7,14,30], smoking participation [5][6][7]14,[31][32][33][34][35][36], and first cigarette initiation [14]. Only one study to date has analyzed the impact of campaign exposure on daily smoking initiation among youth and found no significant cross-sectional association between the two among 8th, 10th, and 12th graders [14].…”
Section: Discussioncontrasting
confidence: 99%
“…Our longitudinal study of cohorts of 12th graders from a nationally representative sample found no evidence that greater exposure to anti-tobacco media campaigns at baseline was associated with any smoking or daily smoking initiation as youth transitioned into adulthood. Our findings are in contrast to the majority of previously published cross-sectional work, including a study analyzing cross-sectional MTF data from the same time period (2000-2015) [14], which found that higher levels of exposure to antitobacco media campaigns are generally associated with lower likelihoods of smoking intentions [3,6,7,14,30], smoking participation [5][6][7]14,[31][32][33][34][35][36], and first cigarette initiation [14]. Only one study to date has analyzed the impact of campaign exposure on daily smoking initiation among youth and found no significant cross-sectional association between the two among 8th, 10th, and 12th graders [14].…”
Section: Discussioncontrasting
confidence: 99%
“…13 Studies of other state campaigns are less rigorous because outcomes are not directly linked with exposure to a media campaign 2,9 or because measures of race/ethnicity were dichotomous (white versus non-white) and intended only as control variables. 14,35 A controlled field experiment designed to evaluate the effect of a 9-month media campaign in four designated market areas in Florida, South Carolina, Texas, and Wisconsin showed that, although there was no overall campaign effect, there was a marginally statistically significant association between living in an intervention media market and current smoking among Hispanic youth (p ¼ .09). 33…”
Section: Effectiveness By Race/ethnicitymentioning
confidence: 99%
“…43,48 ''Health consequences'' was the dominant theme of the effective Massachusetts, North Carolina, and Australia campaigns. 5,14,27,35,50 Evaluations of those campaigns are not included in this analysis because they do not advance our understanding of the effectiveness of this message theme over and above other campaign and ad characteristics. This is because they assess the effectiveness of the campaigns as a whole, without seeking to isolate the role played by the message theme.…”
Section: Message Executionmentioning
confidence: 99%
“…For instance, the national US campaign launched by the Centers for Disease Control and Prevention  called ‘Tips From Former Smokers’ that depicted smoking-related suffering in real people was effective in increasing population-level quit attempts,12 and the personal testimonials campaign (‘TRU’) delivered in North Carolina about negative consequences of tobacco on the smokers’ family decreased smoking prevalence among youths 13. Regarding the use of shocking images, the original versions of the ‘Sponge’ Australian advertisement (1983) and of the Australian ‘Artery’ campaign (1997) were associated respectively with a 3.4%14 and a 1.4% decline in smoking prevalence 15.…”
Section: Introductionmentioning
confidence: 99%